K teorii aktivního vzdělávacího obsahu v transdidaktickém pojetí - Jan Slavík; Tomáš Janík; Jiří Kohout; Tereza Češková; Pavel Mentlík; Petr Najvar (Karolinum Press, 2021)
This theoretical study builds on Fisherman's view of active content as an agent of cognitive change and on Kvasz's theorem that cognitive changes on the level of historical cultural epistemology and cognitive changes on the level of student's personal epistemology can be explain through the same typology. The paper looks for the clarification of this agreement through concepts like "intentionality", "content transformation" and the "instrumentalization of experience". The educational potential of active content between the cultural and the personal level is explained with reference to the concept of "meme", which represents the creation of active content in cultural history as well as the distribution of active content within society and its influence upon an individual. The tools for meme replication in educational environment are learning tasks; they generate cognitive changes in students insomuch as they have sound semantic and logical structure of cognitive schemata. Upon this explanatory basis authors interpret Kvasz's typology of cognitive changes that stems from the analysis of scientific revolutions in the cultural history.